Adaptation of Verticulture Technology in Sustainable and Environmentally Friendly Horticultural Systems - Luh Kadek Pande Sri Astrini; Suluh Dewanto (CV. HEI PUBLISHING INDONESIA, 2025)
The increasing scarcity of agricultural land and the significant impacts of global climate change have created an urgent need for innovative cultivation methods, particularly in the horticulture sector. This study analyzes the adoption of verticulture technology within sustainable horticultural systems across major Indonesian production centers, including West Java, East Java, and North Sumatra. This study employs a descriptive quantitative approach using secondary data from the Central Statistics Agency (BPS), complemented by field surveys and semi-structured interviews with verticulture practitioners. Results indicate that verticulture enhances land-use efficiency by up to 85%, reduces water consumption by 60%, and decreases reliance on synthetic chemical fertilizers by 70%. The technology also contributes to production stability and local food security while maintaining economic viability, with an average return on investment achieved within 3.5 years. These findings support verticulture as a critical urban farming strategy that advances sustainable resource management, food resilience, and socio-economic benefits in Indonesia’s urban and suburban contexts. Further research is recommended to develop inclusive business models and adapt verticulture practices to diverse socio-economic environments to support broader and more sustainable adoption.